Comparison of Mocis latipes biology in artificial diet and in corn and sorghum leaves - Cruz, Ivan; Santos, Jamilton Pereira (Pesquisa Agropecuaria Brasileira, 2014)
The biology of Mocis latipes Gueneé 1852, reared on an artificial bean diet and also on corn and sorghum leaves, was studied at the Entomology Laboratory, in Sete Lagoas, MG, Brazil. There were no significant differences in larval development between individuals reared on corn or sorghum leaves. On the average, the larval, pupal, and larva-adult periods lasted 19.5, 9.6 and 28.9 days, respectivelly. The average pupal weight was 302 mg. Mortality rates were 11.3 and 0.5% for larvae and pupae respectively for individuals reared on corn leaves and 11.5 and 2.9% for sorghum. The artificial diet was unsatisfactory due to the high mortality rate (55%), and also a reduction in the width, length and weight of pupae of 26.1, 14.3 and 38%, respectively, compared to individuals reared on natural diet.
Keywords: biology; insects; larvae; diet